1996
DOI: 10.1152/ajpgi.1996.270.4.g646
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of hepatic sterol 27-hydroxylase by bile acids

Abstract: The study objective was to determine whether and to what extent sterol 27-hydroxylase, the initial step in the "acidic" pathway of bile acid biosynthesis, is regulated by bile acids. Rats were fed diets supplemented with cholestyramine (CT, 5%), cholate (CA, 1%), chenodeoxycholate (CDCA, 1%), or deoxycholate (DCA, 0.25%). When compared with paired controls, sterol 27-hydroxylase and cholesterol 7 alpha-hydroxylase specific activities increased after CT administration by 188 +/- 20% (P < 0.05) and 415 +/- 36% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…However, it is impossible to exclude that it was the high dose of cholate alone that regulated synthesis of both primary bile acids in hamsters. Infusion experiments in rats 10 coordinate down-regulation of cholesterol 7␣-and 27-hydroxylase [36][37][38] has been proposed for the rat, although this has not been confirmed consistently, 35 and species differences may also influence the results. 39 With respect to long-term effects on synthesis from de novo cholesterol, the infusion of conjugated cholate in a low dose and of deoxycholate in a high dose increased the amount of cholate synthesis from de novo cholesterol, most likely mediated by its increased availability, whereas de novo proportions of chenodeoxycholate remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is impossible to exclude that it was the high dose of cholate alone that regulated synthesis of both primary bile acids in hamsters. Infusion experiments in rats 10 coordinate down-regulation of cholesterol 7␣-and 27-hydroxylase [36][37][38] has been proposed for the rat, although this has not been confirmed consistently, 35 and species differences may also influence the results. 39 With respect to long-term effects on synthesis from de novo cholesterol, the infusion of conjugated cholate in a low dose and of deoxycholate in a high dose increased the amount of cholate synthesis from de novo cholesterol, most likely mediated by its increased availability, whereas de novo proportions of chenodeoxycholate remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acid synthesis via 27-hydroxylase (acidic pathway) accounts for a substantial fraction of bile acid synthesis under physiological conditions and after long-term bile drainage, at least in the rat 32,33 and mouse. 34 Additionally, modulation of this alternative pathway may differ from that of the classical cholesterol 7␣-hydroxylation pathway 35 or between species like rats [36][37][38] and rabbits. 39 Therefore, direct quantitation of synthesized end-products is necessary to include all molecular mechanisms relevant for regulation of bile acid synthesis.…”
mentioning
confidence: 99%
“…4,[32][33][34] In vivo, however, multiple cell types are present in the liver, and it is possible that nonparenchymal sinusoidal cells may play a role in mediating cholestatic insults to hepatocytes. 35 In preliminary experiments using transfected primary rat hepatocytes, Karpen et al showed that levels of bile salts similar to those used in the current study suppressed the activity of the rat ntcp promoter.…”
Section: Discussionmentioning
confidence: 99%
“…The "acidic" pathway of bile acid biosynthesis is initiated by the mitochondrial enzyme, sterol 27-hydroxylase (CYP27A1) (1). Oxysterol intermediates of the "acidic" pathway such as 27-hydroxycholesterol and 25-hydroxycholesterol have been shown to be regulators of cholesterol homeostasis (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%